The Implications of the Implementation Style and Middle Management Efforts in Strategy Management Implementation and Public Organisational Performance - Bienmali Kombate; Konan Richard Kouadio (Asian Academy of Management Journal, 2022)
Strategy management implementation (SMI) in developing countries studies is becoming an exciting topic; however, there is a barrier to collect data. Furthermore, a possible mechanism relying on SMI in administration history has acknowledged limited empirical consideration. This paper examined the implication of the implementation style and middle management efforts in the relationship between SMI and organisational performance (OP). Data were collected on a sample of 212 Togolese administrators in eight ministries through structured questionnaires. In contrast to earlier studies in industrialised countries within the context of modernisation and democratisation, which suggested that the logical (M1) or logical-incremental (M3) style(s) is locus to drive changes and enhance OP, the finding revealed that the application of incremental style (M2) was associated with better OP than M1 or M3. Public organisations characterised by traditional bureaucracy and lack of administrative reform program implementation opted for M1 will likely strand and decrease performance.